Biology at the height - Ordóñez, J. Hernando (1952)
Oxygen saturation in the blood of the altitude in Bogota (2.640 meters, is normal or near normal in this stage have been observed the following: abnormal pulse, blood pressure is not modified, the electrocardiogram shows no signs of. anoxemia. were not observed metabolic changes, or breathing or nervous system. from an exceptional way there have been some mild symptoms of chronic mountain sickness. observed a generalized melanosis which is lack of some factors in food and the height seems to have a secondary role in its pathogenesis. need to be studied more special behavior of certain diseases, especially heart disease and lung disease in height. the same can be said of the conduct in height.